Comparison of lyophilized versus liquid modified vaccinia Ankara (MVA) formulations and subcutaneous versus intradermal routes of administration in healthy vaccinia-naïve subjects. Issue 39 (22nd September 2015) - Frey, Sharon E.; Wald, Anna; Edupuganti, Srilatha; Jackson, Lisa A.; Stapleton, Jack T.; Sahly, Hana El; El-Kamary, Samer S.; Edwards, Kathryn; Keyserling, Harry; Winokur, Patricia; Keitel, Wendy; Hill, Heather; et al.
Highlights Lyophilized MVA was more immunogenic than the current liquid formulation of MVA. The lower ID dose of MVA was immunologically non-inferior to the standard SC dose. The ID route resulted in more erythema and/or induration than the SC route. The ID route may increase the number of available doses in an emergency situation.